2017
DOI: 10.37119/ojs2017.v23i2.340
|View full text |Cite
|
Sign up to set email alerts
|

Early Career Teachers’ Evolving Content-Area Literacy Practices

Abstract: Becoming effective teachers is dependent upon a variety of factors intersecting with early career teachers’ beginning teaching experiences. This paper provides a glimpse into ways in which four early career secondary school teachers began to embed literacies into their teaching practices in content areas and how their approaches shifted between the final term of their teacher education program in 2013 and their first year of teaching in 2014. The authors explore three factors that may shape the practices of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…New teachers are often busy just trying to survive (e.g. Murray-Orr and Mitton-Kukner, 2017; Shoval et al, 2010), and one challenge that has been shown to affect teacher attrition is that the preparation during TE does not match the realities of school (Flory, 2016; Ingersoll and Strong, 2011). There is also a risk that novice teachers who lack expected resources and support do not use the knowledge and skills learned in TE (Blankenship and Coleman, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…New teachers are often busy just trying to survive (e.g. Murray-Orr and Mitton-Kukner, 2017; Shoval et al, 2010), and one challenge that has been shown to affect teacher attrition is that the preparation during TE does not match the realities of school (Flory, 2016; Ingersoll and Strong, 2011). There is also a risk that novice teachers who lack expected resources and support do not use the knowledge and skills learned in TE (Blankenship and Coleman, 2009).…”
Section: Introductionmentioning
confidence: 99%